Things have changed (or have they?) tariff protection and environmental concerns in the WTO - Petros C. Mavroidis; Damien J. Neven (Graduate Institute of International and Development Studies, 2018)
This paper considers the APEC and proposed EGA agreements which grant tariff concession in favor of "green" goods. We .nd that the practical significance of the APEC agreement should not be overestimated as it involves modest tariff concessions over a subset of goods which are not heavily traded. Still, these agreements involve a paradigm shift to the extent that they use tariffs concessions negotiated on a purilateral basis as a policy instrument to meet public policy concern, instead of making market access conditional on meeting national regulations. We model the mechanism through which these tariff preferences provide incentives to change production in favor of green goods in exporting countries and highlight the challenges that the implementation of these agreements involve.
Keywords: K40; 330; WTO; APEC; EGA; Tariffs; Terms of Trade; ex outs